Penentuan Persediaan Produk Perishable pada Rumah Tangga: Analisis Faktor dan Strategi dalam Mencapai Efisiensi - Prasetyo, Iwan (Institut Ilmu Sosial dan Manajemen Stiami, 2024)
The low level of public knowledge regarding determining the inventory of perishable products is the knowledge-sharing of community service activities to increase community knowledge and understanding in determining optimal inventory levels in households regarding perishable products. In community service activities using socialization and knowledge-sharing methods, it is hoped that using this method will increase community understanding. Apart from that, the results of the service increase public knowledge and understanding in determining perishable product inventory management and applying it in everyday life to reduce waste.